THERAPY FOR DRUG-RESISTANT SEIZURES: MESIAL TEMPORAL LOBE EPILEPSY - de Farias , Wanderson Santos; da Silva, Uanderson Pereira; da Silva, Jose Augusto Ferreira; Emanuella Maria Lopes Nardoto; Lopes, Gabriel César Dias (Editora Impacto Científico, 2025)
Epilepsies are a set of neurological conditions marked by excessive electrical activity in brain tissue and a propensity for spontaneous epileptic seizures. This is an integrative review. According to the clinical protocol and therapeutic guidelines for epilepsy from the Brazilian Ministry of Health (2015), epilepsy is a chronic brain condition associated with dysfunction of normal brain activity, characterized by the frequency of uninduced epileptic seizures. The bibliographic study on cannabidiol concludes that this substance is promising for inclusion in the range of medications for the treatment of epilepsy.DOI: https://doi.org/10.56238/edimpacto2025.091-037